Water, women, and local social organization in the Western Kenya highlands - Were, Elizabeth; Swallow, Brent M.; Roy, Jessica (International Food Policy Research Institute, 2006)
Safe water is widely recognized as both a fundamental human need and a key input into economic activity. Across the developing world, the typical approach to addressing these needs is to segregate supplies of water for domestic use from water for large-scale agricultural production. In that arrangement, the goal of domestic water supply is to provide small amounts of clean safe water for direct consumption, cleaning, bathing and sanitation, while the goal of agricultural water supply is to provide large amounts of lower quality water for irrigated agriculture. A new third use of water is now being given more attention by researchers: small amounts of water employed in selected household enterprises. This third use may be particularly important for women. There is a potential, therefore, that provision of modest amounts of water to smallholder farmers can enhance household economic production, save labor time for women and girls, and improve family health. This paper adds to the merger literature on the multiple values of improved water supplies – improved health, time savings, and small-scale production for individual farmers and collectives – for the case of a rural community in the western highlands of Kenya. With minimum external support, two groups in this community have managed to install and operate systems of spring protection and piped water to their members’ homesteads. Members of those households, particularly women, have benefited substantially in terms of time savings, health and small-scale production. The experience of this community also illustrates some of the challenges that must be faced for a community to effectively self-organize the investment and maintenance of a communitybased water scheme. There are challenges of finance, gender relations, and conflict over scarce water supplies, group leadership, enforcement of community bi-laws, and policy. Data from a census of springs in the same area show that successful collective action for water management is unusual, but certainly not unique, in this region of Kenya. Although women emerge as the main beneficiaries of improved water management in the community, their substantial contributions are largely hidden behind social norms regarding gender roles and relations. Research methods need to carefully triangulate information sources in order to clarify the very substantial and active roles performed by women. Kenya’s water policy should be modified to better recognize and facilitate small-scale community-based water projects.